Long‐term outcomes of outpatient laser ablation for recurrent non‐muscle invasive bladder cancer: A retrospective cohort study. Issue 2 (13th October 2021) - Grover, Sarika; Raj, Siddarth; Russell, Beth; Mensah, Elsie; Nair, Rajesh; Thurairaja, Ramesh; Khan, Muhammad Shamim; Thomas, Kay; Malde, Sachin
Abstract: Objectives: The objective of this study is to determine the long‐term efficacy and safety of office‐based Holmium:YAG laser ablation for the treatment of recurrent non‐muscle‐invasive bladder cancer (NMIBC). Methods: We retrospectively reviewed the medical records of all consecutive patients who underwent office‐based laser ablation for recurrent bladder cancer between 2008 and 2016. The following data were collected: original histology, date of original histology, date of laser ablation, number of repeat laser ablation procedures required, date of tumor recurrence or progression, number of general anesthesia procedures (transurethral resection or cystodiathermy) required after first laser ablation, and number and severity of complications. Kaplan–Meier survival curves were produced for recurrence‐free survival, progression‐free survival, and overall survival. Results: A total of 97 patients, with an average age of 84 (62–98) years and an average Charlson Comorbidity Index of 6.9 (4–13), were included. The median follow‐up was 61 (2–150) months. Fifty‐five (56.7%) patients presented with tumor recurrence, and the median recurrence‐free survival time was 1.69 years (95% CI 1.20–2.25). Only 9 (9.3%) patients had evidence of tumor progression to a higher grade or stage, 8 (89%) of which initially had low‐grade tumors; however, no patient progressed to muscle‐invasive disease. The median progression‐free survival time was 5.70 years (95% CI 4.10–7.60), and the median overall survival time was 7.60 years (95% CI 4.90–8.70). No patient required emergency inpatient admission after laser ablation. Conclusion: Office‐based Holmium:YAG laser ablation offers a safe and effective alternative method for treating low‐volume, low‐grade recurrent NMIBC, especially in elderly patients with significant co‐morbidity, while avoiding general anesthesia and inpatient admission.